"Breastfeeding" without baby: A longitudinal, qualitative investigation of how mothers perceive, feel about, and practice human milk expression. Issue 3 (12th January 2017) - Felice, Julia P.; Geraghty, Sheela R.; Quaglieri, Caroline W.; Yamada, Rei; Wong, Adriana J.; Rasmussen, Kathleen M.
Abstract: Most American mothers who produce human milk (HM) now pump in place of some or all feeding at the breast, and most American infants are now fed pumped HM. We aimed to investigate mothers' perceptions of, attitudes toward, and practices for pumping and providing pumped HM. Results related to pumping are reported here. We conducted in‐depth, semi‐structured interviews among a diverse sample of 20 mothers who pumped, following each from pregnancy through infant HM‐feeding cessation up to 1 year postpartum. Data were analyzed using thematic analysis with Atlas.ti. Mothers' reasons for pumping changed over time and reflected their needs and desires (e.g., latch difficulty, return to work, and increasing their milk supply). Mothers reported that pump type and quality were important to pumping success and that pumping was time‐consuming, costly, and unpleasant compared to feeding at the breast. Regardless of how often mothers pumped, most felt pumping was necessary to meet their infant HM‐feeding goals and was a welcome means of sharing with other caregivers the bonding opportunity and tasks they associated with feeding infants. Mothers interpreted output from pumping sessions to understand their ability to provide enough milk to meet their infants' needs. Mothers' reasons for pumping may signal constraints to infant HM feeding that may be addressed with policy changes. Mothers' attitudes and perceptions toward pumping indicate that, although pumping fills important and welcome roles for many mothers, the reality of its practice may make it an unacceptable or infeasible substitute for some.